The effect of the MHC locus on autoantibodies in type 1 diabetes - Qu, Hui-Qi (2009)
OBJECTIVE: This study aimed to investigate whether the presence of autoantibodies specific for type 1 diabetes (T1D) is determined by the major genetic susceptibility locus for the disease at the HLA genes, using the T1D Genetics Consortium data. METHODS: We analyzed anti-IA-2 and anti-GAD 65 autoantibody data from 2,282 T1D patients from 1117 multiplex families. HLA genotyping was available for all cases and their parents and association with autoantibody positivity was tested by the transmission disequilibrium test. RESULTS: Association of anti-IA-2 with the HLA genes was detected at high statistical signficance. HLA-DRB1*0401 confers both the strongest type 1 diabetes risk, and positive association of anti-IA-2, whereas the DRB1*03- DQA1*0501-DQB1*0201 haplotype, associated less strongly with T1D, showed a significant negative association with anti-IA-2 positivity. Interestingly, HLA-A*24 is also negatively associated with anti-IA-2, independently of the DRB1*03- DQA1*0501-DQB1*0201 haplotype. No statistically significant association was identified between anti-GAD65 and HLA. CONCLUSIONS: This study highlights that IA-2 as an autoantigen depends on HLA genotype and suggests new insights into the mechanism of loss of immune tolerance.